agCelerant pre-positioned to de-risk 17 million smallholder farms in sub-Saharan Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Since 2015, CCAFS supports the innovative embedment of CGIAR scientific resources inside the African private sector. This PPP sustained the creation by Manobi Africa of agCelerant, an inclusive smallholder value chain orchestration platform based on phygital agriculture. Safely connecting producers with finance, insurance, agro-industry, inputs and advisories to de-risk agricultural investment, agCelerant has been endorsed by Nigeria's Federal Ministry of Agriculture and Rural Development and by the Islamic Development Bank for scaling out to 17 million African smallholder farms.